2017
DOI: 10.18632/oncotarget.22699
|View full text |Cite
|
Sign up to set email alerts
|

Associations between erythropoietin polymorphisms and risk of diabetic microvascular complications

Abstract: We conducted a meta-analysis to evaluate the relationship between erythropoietin (EPO) polymorphisms and diabetic microvascular complications. We searched the PubMed, Embase, Cochrane library, Web of Science, Wanfang, and Chinese National Knowledge Infrastructure databases for appropriate studies. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to evaluate the associations. Ultimately, eight studies consisting of 2,861 cases and 2,136 controls were identified and included in our meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
(29 reference statements)
4
13
0
Order By: Relevance
“…The products of these genes encode insulin (INS) and insulin receptor (INSR), endothelin-1 (EDN1), erythropoietin (EPO), adiponectin (ADIPOQ), interleukin-1β (IL1B), interleukin-6 (IL6), tumor necrosis factor α (TNF), glucagon-like peptide-1 receptor (GLP1R), insulin-like growth factor-1 (IGF1), vascular endothelial growth factor A (VEGFA), C-reactive protein (CRP), nuclear factor, erythroid 2 like 2 (NFE2L2) and neuropeptide Y (NPY). A wide range of biological activities of these molecules is consistent with the concept of their key role in the pathophysiology of diabetic vascular complications [44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Comparative Analysis Of the Gene Network Of Hypoglycemia And Diabetic Vascular Diseasesupporting
confidence: 78%
“…The products of these genes encode insulin (INS) and insulin receptor (INSR), endothelin-1 (EDN1), erythropoietin (EPO), adiponectin (ADIPOQ), interleukin-1β (IL1B), interleukin-6 (IL6), tumor necrosis factor α (TNF), glucagon-like peptide-1 receptor (GLP1R), insulin-like growth factor-1 (IGF1), vascular endothelial growth factor A (VEGFA), C-reactive protein (CRP), nuclear factor, erythroid 2 like 2 (NFE2L2) and neuropeptide Y (NPY). A wide range of biological activities of these molecules is consistent with the concept of their key role in the pathophysiology of diabetic vascular complications [44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Comparative Analysis Of the Gene Network Of Hypoglycemia And Diabetic Vascular Diseasesupporting
confidence: 78%
“…Tong et al (2008) implicated the opposite T allele as the risk allele for PDR as well as for end-stage renal disease in European-Americans, while Gong (2015) associated the aforementioned allele with higher DR risk. All four aforementioned studies along with another four of Asian populations were included in the recent meta-analysis conducted by Li et al (2017). While their subgroup analysis revealed an association between the rs1617640 polymorphism and diabetic microvascular complications, the association with increased risk for solely DR has not been found in any genetic model neither in Asians nor in Australians.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies analysed the connection between rs1617640 and microvascular complications of diabetes. Three of those confirmed the existence of a statistically significant association between rs1617640 and microvascular complications of DM (Tong et al 2008;Abhary et al 2010;Fan et al 2016), while in the others a significant relationship could not be proven (Hosseini et al 2015;Song et al 2015;Li et al 2017;Dame et al 2018).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…There are mixed reports regarding EPO's polymorphism and DR. While some studies have demonstrated an association between rs551238, rs1617640, and rs507392 and an increased risk of developing PDR [37][38][39], a recent 2020 meta-analysis could not find such an association [148], and an association was only observed between rs551238 and DR in a 2017 meta-analysis study [149].…”
Section: Erythropoietin Genementioning
confidence: 99%